Study of causal factors in the use of MIS to design wooden furniture of small and medium industries in Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This integrative research aimed to study and develop a causal model of MIS-assisted wooden furniture design of small and medium industries in terms of designer competence, management, innovation and technology and cost. The operating procedure consisted of quantitative research and using stratified sampling methods from 2,898 populations. Informants were operators, owners, managers, or assignees of 240 locations. Qualitative research would select 7 target groups using the specific method of selection. Confirmation of research results was done using a focus group, with ten management experts and related experts in wood furniture design participating in the focus group. The results of the study revealed that the key factors affecting the use of MIS in the design of the wood furniture industry were designer competence factors, management factors, innovation and technology, and cost factors. These three factors directly and indirectly influenced MIS-assisted wooden furniture design for small and medium industries in Thailand. Goodness of Fit Index values: 2=54.80, df = 44, 2/df = 1.24, p-value = 0.13, CFI = 0.99, GFI = 0.96, AGFI = 0.93, SRMR = 0.04, RMSEA = 0.032